IMPLEMENTASI MODEL EDUKASI BIMBINGAN PADA IBU HAMIL UNTUK PENCEGAHAN RESIKO STUNTING DIKABUPATEN BANYUMAS : STUDI KUALITATIF - Inggar Ratna Kusuma; Wilis Dwi Pangesti (IAKMI South Tangerang Branch, 2022)
Abstract Background: Based on the 2021 Indonesian Toddler Nutrition Status Survey (SSGBI), the prevalence of stunting in Indonesia is still high, namely 24.4 percent or 5.33 million toddlers (1). One of the causes of stunting is malnutrition when the baby is in the womb and in the early stages of the baby's birth. The problem of malnutrition in pregnant women can cause low birth weight babies (LBW), malnutrition in toddlers and predispose to edit(2). One of the efforts to prevent stunting during pregnancy is through nutrition education and coaching for pregnant women. The coaching method improves the healthy lifestyle of pregnant women. improve the ability of pregnant women to regulate their nutritional patterns and nutrition during pregnancy Objective To explore coaching methods for pregnant women to increase knowledge about stunting prevention. Method: This research method is a qualitative research using a phenomenological design. The research was conducted in Banyumas Regency. Selection of purposive sampling informants. Data collection through in-depth interviews and analyzed using the Miles and Huberman method Result: The results of this study explored the nutritional coaching educational model for pregnant women, which is an educational model that combines education through pregnant women classes, home visits and the use of WhatsApp groups as an educational tool. Material development includes the concept of self-management, setting goals, planning, actions related to the nutritional status of pregnant women towards balanced nutrition, and explaining healthy eating patterns in pregnant women. Information about healthy sanitation. the importance of exclusive breastfeeding and healthy parenting for toddlers Conclusion: The conclusion of the nutritional coaching educational model for pregnant women requires a joint commitment from midwives as coaches and pregnant women so that the main goal of increasing stunting prevention knowledge on healthy nutritional status during pregnancy can be achieved. Keywords: Coaching Education Model, pregnant women, prevention of stunting. Abstrak Latar belakang: Berdasarkan Survei Status Gizi Indonesia (SSGI) 2021, prevalensi stunting di Indonesia masih tinggi yaitu 24,4 persen atau 5,33 juta balita. Penyebab stunting salah satunya kekurangan gizi ketika janin dalam kandungan dan pada masa awal bayi lahir. Masalah kekurangan gizi ibu hamil dapat menyebabkan Berat Badan Bayi Lahir Rendah (BBLR). Upaya untuk mencegah stunting selama hamil salah satunya melalui edukasi dan bimbingan gizi pada ibu hamil. Metode bimbingan diharapkan dapat meningkatkan gaya hidup sehat ibu hamil. Meningkatkan kemampuan ibu hamil mengatur pola gizi dan nutrisinya selama hamil Tujuan: Mengeksplorasi bagaimana implementasi keberlanjutan metode bimbingan ibu hamil untuk meningkatkan pengetahuan mengenai pencegahan stunting setelah pemberian intervensi Metode Penelitian ini merupakan penelitian kualitatif menggunakan desain case study. Penelitian dilakukan di Kabupaten Banyumas. Pemilihan informan purposive sampling. Informan primer meliputi Ibu hamil dan bidan sebanyak 25 orang. Validasi data hasil wawancara mendalam dilakukan dengan melakukan triangulasi melalui informan sekunder yakni Ahli gizi Puskesmas, Dosen Gizi di Universitas, Dokter Umum sebanyak 5 orang. Pengambilan data melalui wawancara mendalam dan dianalisis dengan menggunakan Miles and Huberman method Hasil: Penelitian ini implementasi metode edukasi bimbingan gizi pada ibu hamil setelah pemberian intervensi masih kurang optimal karena bidan selaku coach/pembimbing masih terfokus pada pelayanan kebidanan yang tidak holistik. Faktor pendorong implementasi meliputi pelayanan yang diberikan oleh bidan, motivasi ibu hamil untuk berubah, dukungan sosial, respon positif terhadap topik bimbingan manajemen diri dan pola asuh. Faktor penghambat meliputi faktor internal individu (tidak konsisten) dan respon negative terhadap topik sanitasi sehatn Kesimpulan: Keberlanjutan implementasi model edukasi bimbingan gizi pada ibu hamil memerlukan komitmen bersama dari bidan selaku pembimbing dan ibu hamil agar tujuan utama perubahan perilaku peningkatan pengetahuan pencegahan stunting status gizi sehat selama hamil dapat tercapai.